Pemberdayaan Ibu-Ibu PKK Untuk Penguatan Ekonomi Kreatif Melalui Pelatihan Pembuatan Kripik Tempe - Justita Dura; Fadilla Cahyaningtyas; Mohammad Bukhori; Syaiful Bahri; Mariana Puspa Dewi; Mulyaningtyas (CV. Multi Kreasi Media, 2023)
The human resources of Kasri Village, Bululawang District, are the number of PKK mothers who take care of the household. These assets unfortunately have not been honed and managed properly. To increase the productivity of PKK mothers, they must be able to take part in positive activities and help the family economy during the pandemic. The purpose of this activity is to encourage human resources, especially PKK mothers who are only housewives, to participate in useful activities. These Kripik Tempe products can be resold, increasing family income. Training methods in Kasri Bululawang Village The purpose of this program is to equip PKK mothers with training with the aim of increasing family and village incomes and encouraging them to become entrepreneurs, so that in the end they can contribute to the economic improvement of Kasri Village.